Monitoring sweep efficiency of low salinity waterflooding in sandstone reservoir using radioactive tracer: article - Zaidi, Zafirah; Rosli, Nor Roslina; Mohammadian, Erfan; Othman, Noraishah (2019)
Waterflooding is a common secondary recovery oil extraction method that can enhance oil recovery up to 45 percent overall recovery factor. Waterflooding is commonly used due to its availability, cost effectiveness and simplicity. Sweep efficiency is to determine the effectiveness of oil recovery. Radioactive tracer was introduced to get the optimum RTD model which indicate the mechanism of the system. Sweep efficiency was assumed to increase its value when low salinity brine is used as compared to seawater injection due to capillary pressure, interfacial tension and wettability. In this study, low salinity brine with value of 0.5 g/ L NaCl, 1.0 g/L NaCl and 1.5 g/L NaCl were injected into packed column. The sandstone sample were analysed using FESEM to analyse for chemical composition of rock. Sweep efficiency was analysed with and without the use of radioactive tracer. Technetium-99m (Tc-99m) radioisotope with half-life of 6 hours was injected into the column. Results from radioactive tracer test showed that the optimum RTD model for this system is perfect mixer in series with exchange model which indicate the mobilization of oil from attached fine particle. The percent oil recovery decreased with increasing brine salinity. Sweep efficiency monitored using radioactive tracer increase for lower salinity solution, LSW and 500 ppm, 39.49% and 41.36% respectively. Volumetric sweep efficiency decreases as salinity increase. This study can conclude that low salinity NaCl brine gives higher volumetric sweep efficiency.